Website-Based Petty Cash Management Accounting Information System Case Study PT.Haleyora Power Karawang - Hasmi Hasibuan; Dede Firmansyah Saefudin (Universitas Islam Kuantan Singingi, 2022)
A website-based information system is a technological tool that helps users manage data on a small and medium-to-large scale by providing precise and accurate information. PT. Haleyora Power is one of the companies engaged in the electricity supply industry, which currently processes petty cash funds still using written records in books and the Microsoft Excel application. The level of supervision of outgoing funds is relatively low, and the risk of losing report data or reporting data damage due to activity occurs every day and sometimes accidentally. To minimize this, petty cash management can be implemented in the form of a website-based application through a petty cash system that includes petty cash receipts, petty cash disbursement procedures, and petty cash reports. In this case, the waterfall method is very suitable for creating a petty cash system as needed. The petty cash system created can make the procedure for disbursing petty cash funds more structured and provide convenience in data processing so that the reporting process at PT becomes better. Haleyora Power.